Ayudenme porfavo:(
a) 5 + (-3) -6
b) 14 + (-9) + (-9)
c) -1 - 3 – (- 9) + (-5)
d) 17 + (-8) + (-8)
e) -2 + (-3) +4 – (-3) -5
f) -5 -15 +4 +15
g) 2 -3 + (-5) + (-3)
Respuestas
Respuesta dada por:
0
Respuesta:
-4
-4
0
1
2
-1
-9
Explicación paso a paso:
5+(-3)-6= 5-3-6= 5-9= -4
14+(-9)+(-9)=14-9-9=14-18=-4
-1-3-(-9)+(-5)= -1-3+9-5= -9+9=0
17+(-8)+(-8)=17-8-8=17-16=1
-2+(-3)+4-(-3)-5=-2-3+4+3=-5+7=2
-5-15+4+15=-20+19=-1
2-3+(-5)+(-3)=2-3-5-3=2-11=-9
Preguntas similares
hace 2 años
hace 2 años
hace 2 años
hace 5 años
hace 5 años